2017
DOI: 10.5604/01.3001.0010.6760
|View full text |Cite
|
Sign up to set email alerts
|

Renal vascularization anomalies in the Polish population

Abstract: Awareness and preoperative assessment of the venous system before abdominal aortic surgery, isolated collection of renal venous blood samples, and urological or kidney transplantation procedures is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
3
9
0
Order By: Relevance
“…Similarly to our results, most of the studies reported that the incidence of RLRV variations was higher than that of CLRV variations (4,8,10,(13)(14)(15)(16). However, some studies found that the incidence of CLRV variations higher that RLRV variations (5,7,9,11).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly to our results, most of the studies reported that the incidence of RLRV variations was higher than that of CLRV variations (4,8,10,(13)(14)(15)(16). However, some studies found that the incidence of CLRV variations higher that RLRV variations (5,7,9,11).…”
Section: Discussionsupporting
confidence: 88%
“…The results of our study show that the incidence of total LRV variations in the Turkish population is similar to that of other races (6,7,9,16,17).…”
Section: Discussionsupporting
confidence: 76%
“…The percentage of variations in the structure of the venous system was also high. Pick and Anson [21] observed 14.4% of such cases, while in our previous investigations the abovementioned amounted to 33.8% [28].…”
Section: Introductionmentioning
confidence: 61%
“…The existence of such anatomical variants should be taken under consideration, in the prevention of bleeding during retroperitoneal space and abdominal aortic surgery [2,3]. The mentioned anomalies result from the complicated development of the vasculorenal system, which was thoroughly described in our previous studies [27,28]. Generally speaking, an embryo 14-16 mm in length (6-8 weeks of development), is subjected to mesonephros ascend from the pelvis to the lumbar area with simultaneous atrophy of lower arteries and the development of novel abdominal aortic vessels [21,29].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation